HUBUNGAN TINGKAT KESEPIAN DENGAN DURASI PENGGUNAAN MEDIA SOSIAL PADA MAHASISWA KEPERAWATAN DI UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA - Nanda Dwi Rizky Fadillah; Rizqi Wahyu Hidayati (HEALTHY BEHAVIOR JOURNAL, 2025)
Background : Users of internet worldwide experience an increase which might be psychologically disruptive, especially for students who are the largest internet users. Some students state that loneliness was the cause, and individuals experiencing the loneliness would divert their attention to playing with their phones. This was true for nursing students (undergraduate) at Universitas Jenderal Achmad Yani Yogyakarta, who only have seven semesters, which makes their schedules busier and they only have little time to build social relation with friends resulting in loneliness. Objective : This research aims to reveal the correlation between level of loneliness and the duration of social media use on nursing students at Universitas Jenderal Achmad Yani Yogyakarta. Methods : This research applied non-experimental quantitative method, and implemented cross sectional approach. The sample technique used was proportionate stratified random sampling technique involving 77 students in accordance with the inclusive and exclusive criteria. The method of data collection used UCLA Loneliness Scale Version 3 questionnaire and the duration of social media use. Both questionnaires had previously undergone validity and reliability testing by earlier researchers, and the results showed that the questionnaires were appropriate for use in the study. The data collection for this study was carried out from May 27 to June 5,2025. Moreover, the data were analyzed using univariate and bivariate analyses with Gamma test. Result : The majority of the students experienced moderate loneliness were 72 students (93,5%) with the duration of (≥7 hours) of 30 students (39%). The correlation results were r=0,667 and p-value 0,038. Conclusion : The institution is expected to provide psychological guidance or counseling services that are easily accessible to students to help them manage loneliness.